ON A THREE-DIMENSIONAL NONLINEAR DIFFERENTIAL SYSTEM - Tigan, Gheorghe (Matematichki Bilten, 2006)
Insights on a three dimensional nonlinear system are presented in this paper. The system possesses three equilibrium points one of which is the origin \(O(0,0,0)\) whose analysis in the degenerate case is performed. It is also pointed out that \(O(0,0,0)\) undergoes pitchfork bifurcations.